2010
DOI: 10.1111/j.1365-2028.2010.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

The cascading effects of elephant presence/absence on arthropods and an Afrotropical thrush in Arabuko‐Sokoke Forest, Kenya

Abstract: Although studies have explored how habitat structure and disturbance affect arthropod communities, few have explicitly tested the effects of both structure and disturbance level across trophic levels and phyla. We present here the results of a study conducted in the Arabuko‐Sokoke Forest (ASF) of coastal Kenya, in which abundance of arthropods and one of their avian predators, the East Coast Akalat Sheppardia gunning sokokensis was compared in relatively undisturbed habitat (outside elephant roaming areas) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Some studies have indicated that akalats need an open understory, thriving in forest areas that are not too dense but have some vegetation cover and leaf litter in which they can forage (Matiku et al 2000, Nemeth and. However, in a recent study conducted in the Mixed forest of ASF, it was found that this effect diminishes in forests that are 'too open' -specifically, akalat densities are lower in areas with little vegetation 1-2 m off the ground (Banks et al 2010). Sheppardia gunningi's preference for Cynometra forest and thicket may therefore be a function of vegetation density in the sampling areas.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Some studies have indicated that akalats need an open understory, thriving in forest areas that are not too dense but have some vegetation cover and leaf litter in which they can forage (Matiku et al 2000, Nemeth and. However, in a recent study conducted in the Mixed forest of ASF, it was found that this effect diminishes in forests that are 'too open' -specifically, akalat densities are lower in areas with little vegetation 1-2 m off the ground (Banks et al 2010). Sheppardia gunningi's preference for Cynometra forest and thicket may therefore be a function of vegetation density in the sampling areas.…”
mentioning
confidence: 90%
“…More generally, studies on large herbivores indicate that they can negatively impact bird diversity and abundance, with higher densities in areas of herbivore exclusion (Ogada et al 2008). Furthermore, elephants may indirectly affect some bird populations by altering vegetation composition as well as habitat critical to the survival of arthropods important to their diets (Skarpe et al 2004, Banks et al 2010. Elephants in ASF have been contained within the reserve by an electrified fence, which was begun to be put in place approximately 10 years ago.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, understanding of the factors influencing invertebrate taxonomic richness and diversity at both local and regional scales is important for conserving biodiversity and for maintaining ecosystem services. Dung beetles are known to represent an important functional component of the animal fauna found in tropical forests (Krell-Westerwalbesloh et al 2004;Banks et al 2010) as they provide several key ecological functions such as seed dispersal, parasite suppression and dung removal (Nichols et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…, 2009), habitat fragmentation (Dias et al. , 2006), habitat disturbance (Banks et al. , 2010), altitude (Sabu, Vineesh & Vinod, 2008), nutrient levels (McGlynn et al.…”
Section: Introductionmentioning
confidence: 99%